Visualising the Dhammakāya through a Buddha Image: The Dhammakāya Text and Its Significance for Traditional Tai–Khmer Buddhist Practices - Malasart, Woramat (Religions, 2023)
The Dhammakāya Gāthā is a Pāli Buddhist prose text that has been circulated within the cross-cultural/translocal sphere of Tai–Khmer Buddhism for over five centuries. Its earliest extant version appears on the “Braḥ Dhammakāya inscription”, an engraved stone slab from the Stūpa of Wat Suea, Phitsanulok, Thailand, dated to 1549 CE. The Dhammakāya text consists of three parts. The first part identifies the knowledge and qualities/virtues of the Buddha with physical attributes of his body. The second part is the verses in praise of the Buddha’s resplendent body qua the dhammakāya. The third section exhorts one in the yogāvacara lineage (a practitioner of spiritual discipline, i.e., a meditator) to recollect the dhammakāya, in order to attain the state of Buddhahood. The Gāthā was well known in the Tai–Khmer cultural sphere during the pre-modern period, but today, it is little used in modern practices. In this paper, I will analyse textual and paratextual elements of the Dhammakāya Gāthā to uncover the doctrinal meanings underlying the Gāthā and reveal the unique and unusual meditation practice called the Dhammakāyānussati, “Recollection of the Dhammakāya”. I argue that the study of the Dhammakāya Gāthā enables us to understand the unique Buddhist practice: reciting [the Dhammakāya text], constructing [the image of the Buddha] and visualising [the dhammakāya embodied in the image], contributing to what we call “Buddhānussati” in the context of Tai–Khmer Buddhism.